Bathyraja cousseauae sp.n.: A New Softnose Skate from the Southwestern Atlantic (Rajiformes, Rajidae) - Díaz de Astarloa, Juan Martín (2004)
A new species of softnose skate, Bathyraja cousseauae, is described from two adult and 19 juvenile specimens collected from different localities of the southwestern Atlantic. Bathyraja cousseauae is distinguished from all other southwestern Atlantic softnose skate species by its color pattern, squamation pattern of dorsal surface, lack of interspace between dorsal fins, and clasper morphology. The new species has a round pale area ocellus-like, margined with dark brown on posterior part of each pectoral base of dorsal surface, paler and dark spots over the disk, a continuous row of 21–27 median thorns from nuchal region to first dorsal fin and upper side of disc densely covered with dermal denticles. Males have rod-shaped claspers not expanded at proximal section of glans as it does in Bathyraja brachyurops. Besides the external morphological features, skeletal characteristics (neurocranium, scapulocoracoids, and claspers) are also described and illustrated here.Bathyraja cousseauae, is described from two adult and 19 juvenile specimens collected from different localities of the southwestern Atlantic. Bathyraja cousseauae is distinguished from all other southwestern Atlantic softnose skate species by its color pattern, squamation pattern of dorsal surface, lack of interspace between dorsal fins, and clasper morphology. The new species has a round pale area ocellus-like, margined with dark brown on posterior part of each pectoral base of dorsal surface, paler and dark spots over the disk, a continuous row of 21–27 median thorns from nuchal region to first dorsal fin and upper side of disc densely covered with dermal denticles. Males have rod-shaped claspers not expanded at proximal section of glans as it does in Bathyraja brachyurops. Besides the external morphological features, skeletal characteristics (neurocranium, scapulocoracoids, and claspers) are also described and illustrated here.Bathyraja cousseauae is distinguished from all other southwestern Atlantic softnose skate species by its color pattern, squamation pattern of dorsal surface, lack of interspace between dorsal fins, and clasper morphology. The new species has a round pale area ocellus-like, margined with dark brown on posterior part of each pectoral base of dorsal surface, paler and dark spots over the disk, a continuous row of 21–27 median thorns from nuchal region to first dorsal fin and upper side of disc densely covered with dermal denticles. Males have rod-shaped claspers not expanded at proximal section of glans as it does in Bathyraja brachyurops. Besides the external morphological features, skeletal characteristics (neurocranium, scapulocoracoids, and claspers) are also described and illustrated here.Bathyraja brachyurops. Besides the external morphological features, skeletal characteristics (neurocranium, scapulocoracoids, and claspers) are also described and illustrated here.